Clinical and CT Scan Evaluation of Temporomandibular Joints with Osteoarthritis and Rheumatoid Arthritis - Abhijeet Deoghare; Shirish S Degwekar (Wolters Kluwer Medknow Publications, 2010)
Temporomandibular joint disorders refer to a complex and poorly understood set of conditions, manifested by pain in the area of jaw and associated muscles and limitations in the ability to make normal movements like mastication, speech and swallowing. Arthritis as it affects other joints also affects temporomandibular joint (TMJ). The present study was undertaken to study the clinical aspects of patents with osteoarthritis and rheumatoid arthritis of TMJ supplemented by CT scan of joints to study the radiological changes and to find out if there was any correlation between them.